Crisis of values and education as a result of postmodernism (2013)
This paper sets out an analysis of the relation-ship between Education and Postmodernism, and enquires about the impossibility to edu-cate citizens with defined values towards so-ciety’s co-existence in a postmodern culture. In order to understand postmodernism, the concept of modernism was revised and impli-cations of postmodern conception in education, environment and other areas of knowledge were studied. In conclusion, postmodern con-ceptions lead to a society with high levels of uncertainty regarding which way to follow in order to solve daily life problems, something which, from a psychological perspective, gen-erates anxiety, nihilism, and makes social sus-tainability unfeasible